2019
DOI: 10.1111/bju.14915
|View full text |Cite
|
Sign up to set email alerts
|

Update on the guideline of guidelines: non‐muscle‐invasive bladder cancer

Abstract: Non‐muscle‐invasive bladder cancer (NMIBC) is the most common form of bladder cancer, with frequent recurrences and risk of progression. Risk‐stratified treatment and surveillance protocols are often used to guide management. In 2017, BJUI reviewed guidelines on NMIBC from four major organizations: the American Urological Association/Society of Urological Oncology, the European Association of Urology, the National Comprehensive Cancer Network, and the National Institute for Health and Care Excellence. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 64 publications
2
57
0
Order By: Relevance
“…Risk factors for recurrence are the number of primary tumors, the university, the degree of infiltration and the recurrence probability (especially whether the recurrence time is within 3 months after the surgery), etc., while pathological grade and stage of tumors are associated with tumor progression [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for recurrence are the number of primary tumors, the university, the degree of infiltration and the recurrence probability (especially whether the recurrence time is within 3 months after the surgery), etc., while pathological grade and stage of tumors are associated with tumor progression [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…It is a retrospective cohort study to evaluate the impact of non-compliance to standardized risk-adjusted surveillance and treatment in NMIBC. We have used the EAU risk strati cation and surveillance protocol as a reference which is widely accepted and used in most European centres as we don't have national guidelines [8].…”
Section: Methodsmentioning
confidence: 99%
“…The patients were distributed into three main risk group categories according to the EAU risk strati cation [8]. The largest group was the high-risk group which contains 63 patients (71.5%), while the low and intermediate group entails 25 patients (28.5%); (Table 2B).…”
Section: Demographic and Clinical Presentationmentioning
confidence: 99%
“…39,40 Furthermore, all updated recommendations were collected and compared in a new guideline. 41 Recently, the Bladder Cancer Advocacy Network (BCAN) released a joint statement with representatives of different urological societies to also help physicians in the current framework. The consensus of general recommendations to address BCG shortages is described below.…”
Section: Variations In Clinical Guidelines Recommendationsmentioning
confidence: 99%
“…Priming is performed in each trial with Tokyo BCG 31 or RUTI (a therapeutic vaccine for tuberculosis). 41,49 It is worth noting that Ji et al (2019) recently demonstrated the safety of BCG priming in NMIBC patients as well as the different responses of enhanced innate effector cells against some specific BC cell lines, suggesting a potential BCG resistance mechanism that could explain BCG nonresponsivity in some individuals. 50 On the other hand, optimum maintenance schedule has not been clarified.…”
Section: Modification Of Schedules Priming-boosting Strategymentioning
confidence: 99%